Prevalence Of HIV Infection Among Persons Attending Integrated Counseling and Testing Centre, Ambajogai - Sapana S Madkar; S L Nilekar; AJ Vankudre (Medsci Publications, 2011)
Aim: Human immunodeficiency virus (HIV)/ Acquired immunodeficiency syndrome (AIDS) is increasing at an alarming rate globally. It has now become a major challenge and threat to public health. Estimating the HIV prevalence can be helpful to plan and implement preventive strategies. Hence, the study was undertaken to know the prevalence of HIV infection among persons attending Integrated Counseling and Testing Centre, Ambajogai. Material and Method: All the persons attending ICTC of S.R.T.R. Medical College, Ambajogai were counseled over a period from September 2007 to September 2009. Blood sample were collected only from those persons who signed informed consent for HIV testing. Serum was separated and tested for HIV antibodies as per National AIDS Control Organization (NACO) guidelines. Strict confidentiality was maintained. Reports were issued only after post-test counseling. Result: Out of the total 11380 samples tested, 1286(11.3%) samples were found to be HIV seropositive. Male to female ratio in HIV seropositive was 3.09:1. Maximum seropositivity i.e.40.82% was found in the age group of 30-39 years followed by 20-29 years age group. Conclusion: In the present study, prevalence of HIV in persons attending ICTC was found to be 11.3%.